The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

Brominated Flame Retardants in Antarctic Air in the Vicinity of Two All-Year Research Stations - Bengtson Nash, Susan Maria; Wild, Seanan; Broomhall, Sara; Bohlin-Nizzetto, Pernilla (Atmosphere, 2021)
Continuous atmospheric sampling was conducted between 2010–2015 at Casey station in Wilkes Land, Antarctica, and throughout 2013 at Troll Station in Dronning Maud Land, Antarctica. Sample extracts were analyzed for polybrominated diphenyl ethers (PBDEs), and the naturally converted brominated compound, 2,4,6-Tribromoanisole, to explore regional profiles. This represents the first report of seasonal resolution of PBDEs in the Antarctic atmosphere, and we describe conspicuous differences in the ambient atmospheric concentrations of brominated compounds observed between the two stations. Notably, levels of BDE-47 detected at Troll station were higher than those previously detected in the Antarctic or Southern Ocean region, with a maximum concentration of 7800 fg/m3. Elevated levels of penta-formulation PBDE congeners at Troll coincided with local building activities and subsided in the months following completion of activities. The latter provides important information for managers of National Antarctic Programs for preventing the release of persistent, bioaccumulative, and toxic substances in Antarctica.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; menneskelig påvirkning; miljøgifter; miljøovervåking; målinger

Ionosfæriske scintillasjoner på GNSS-signaler over Dronning Maud Land, Antarktis: statistikk og kasusstudier - Skjæveland, Arnlaug Høgås (Universitetet i Oslo, 2020)
I denne oppgaven er forekomsten av fasescintillasjoner på GNSS-signaler over deler av Dronning Maud Land i Antarktis kartlagt, ved bruk av scintillasjonsmottakere på Troll stasjonen (geografiske koordinater: 72.0◦S, 2.5◦Ø, magnetiske koordinater: 62.8◦S, 47.8◦Ø) og SANAE IV (geografiske koordinater: 71.7◦S, 2.8◦V, magnetiske koordinater: 62.0◦S, 45.0◦Ø). Ionosfæren i dette området er lite studert tidligere, og dette er de første resultatene som presenteres fra det nylig etablerte Troll ionosfæriske observatoriet. Den første delen av oppgaven er en statistisk studie hvor forekomsten av scintillasjoner i 2018 er kartlagt. Hovedfunnet i denne studien er at høye fasescintillasjoner kun forekommer ved høy geomagnetisk aktivitet, forekomsten av scintillasjoner er høyere postmidnatt enn premidnatt og at scintillasjoner forekommer både innenfor og nord for den statistiske auroraovalen. I denne oppgaven er det også gjennomført to kasusstudier, en fra februar 2018 og en fra mars 2018. Kasusstudiene brukte satellittdata fra solvinden, Swarm, DMSP og bakkebaserte instrumenter: scintillasjonsmottakere, magnetometere og Superdarn, fra både den nordlige og sørlige halvkule. Hovedfunnene fra kasusstudiene er at scintillasjoner på Troll og Sanae kan assosieres med partikkelnedbør, sterke vestgående strømmer og høye konveksjonshastigheter. De viste også en hvis symmetri i forekomsten av scintillasjoner, men scintillasjonene var kraftigere og var til stede over en lengre tidsperiode i Antarktis enn på Færøyene.
Keywords: Antarktis; Dronning Maud Land; Troll forskningsstasjon; aurora; geomagnetiske stormer; ionosfæren; romfysikk; sørlys

Ground-based measurements of total ozone column amount with a multichannel moderate-bandwidth filter instrument at the Troll research station, Antarctica - Sztipanov, Milos; Tumeh, Lubna; Li, Wei; Svendby, Tove; Kylling, Arve; Dahlback, Arne; Stamnes, Jakob J; Hansen, Georg; Stamnes, Knut (Applied Optics, 2020)
Combining information from several channels of the Norwegian Institute for Air Research (NILU-UV) irradiance meter, one may determine the total ozone column (TOC) amount. A NILU-UV instrument has been deployed and operated on two locations at Troll research station in Jutulsessen, Queen Maud Land, Antarctica, for several years. The method used to determine the TOC amount is presented, and the derived TOC values are compared with those obtained from the Ozone Monitoring Instrument (OMI) located on NASA’s AURA satellite. The findings show that the NILU-UV TOC amounts correlate well with the results of the OMI and that the NILU-UV instruments are suitable for monitoring the long-term change and development of the ozone hole. Because of the large footprint of OMI, NILU-UV is a more suitable instrument for local measurements.
Keywords: Dronning Maud Land; Troll forskningsstasjon; meteorologi; overvåkning; ozonhull; ozonlaget; ultrafiolett stråling

Annual cycle of Antarctic baseline aerosol: controlled by photooxidation-limited aerosol formation - Fiebig, Markus; Hirdman, David; Lunder, Chris R; Ogren, John A; Solberg, Sverre; Stohl, Andreas; Thompson, Rona L (Atmospheric Chemistry and Physics (Print), 2014)
This article investigates the annual cycle observed in the Antarctic baseline aerosol scattering coefficient, total particle number concentration, and particle number size distribution (PNSD), as measured at Troll Atmospheric Observatory. Mie theory shows that the annual cycles in microphysical and optical aerosol properties have a common cause. By comparison with observations at other Antarctic stations, it is shown that the annual cycle is not a local phenomenon, but common to central Antarctic baseline air masses. Observations of ground-level ozone at Troll as well as backward plume calculations for the air masses arriving at Troll demonstrate that the baseline air masses originate from the free troposphere and lower stratosphere region, and descend over the central Antarctic continent. The Antarctic summer PNSD is dominated by particles with diameters <100 nm recently formed from the gas-phase despite the absence of external sources of condensible gases. The total particle volume in Antarctic baseline aerosol is linearly correlated with the integral insolation the aerosol received on its transport pathway, and the photooxidative production of particle volume is mostly limited by photooxidative capacity, not availability of aerosol precursor gases. The photooxidative particle volume formation rate in central Antarctic baseline air is quantified to 207 ±4 μm3/(MJ m). Further research is proposed to investigate the applicability of this number to other atmospheric reservoirs, and to use the observed annual cycle in Antarctic baseline aerosol properties as a benchmark for the representation of natural atmospheric aerosol processes in climate models.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; klimamodeller; miljøgifter

Long-term monitoring of persistent organic pollutants (POPs) at the Norwegian Troll station in Dronning Maud Land, Antarctica - Kallenborn, Roland; Breivik, Knut; Eckhardt, Sabine; Lunder, C R; Manø, S; Schlabach, Martin; Stohl, Andreas (Atmospheric Chemistry and Physics (Print), 2013)
A first long-term monitoring of selected persistent organic pollutants (POPs) in Antarctic air has been conducted at the Norwegian research station Troll (Dronning Maud Land). As target contaminants 32 PCB congeners, α- and γ-hexachlorocyclohexane (HCH), trans- and cis-chlordane, trans- and cis-nonachlor, p,p'- and o,p-DDT, DDD, DDE as well as hexachlorobenzene (HCB) were selected. The monitoring program with weekly samples taken during the period 2007–2010 was coordinated with the parallel program at the Norwegian Arctic monitoring site (Zeppelin mountain, Ny-Ålesund, Svalbard) in terms of priority compounds, sampling schedule as well as analytical methods. The POP concentration levels found in Antarctica were considerably lower than Arctic atmospheric background concentrations. Similar to observations for Arctic samples, HCB is the predominant POP compound, with levels of around 22 pg m−3 throughout the entire monitoring period. In general, the following concentration distribution was found for the Troll samples analyzed: HCB > Sum HCH > Sum PCB > Sum DDT > Sum chlordanes. Atmospheric long-range transport was identified as a major contamination source for POPs in Antarctic environments. Several long-range transport events with elevated levels of pesticides and/or compounds with industrial sources were identified based on retroplume calculations with a Lagrangian particle dispersion model (FLEXPART).
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; miljøgifter; miljøovervåking

The effect of energetic electron precipitation on middle mesospheric night-time ozone during and after a moderate geomagnetic storm - Daae, Marianne; Espy, Patrick J; Nesse Tyssøy, Hilde; Newnham, David A; Stadsnes, Johan; Søraas, Finn (Geophysical Research Letters, 2012)
Using a ground-based microwave radiometer at Troll Station, Antarctica (72°S, 2.5°E,L = 4.76), we have observed a decrease of 20–70% in the mesospheric ozone, coincident with increased nitric oxide, between 60 km and 75 km altitude associated with energetic electron precipitation (E > 30 keV) during a moderate geomagnetic storm (minimum Dst of −79 nT) in late July 2009. NOAA satellite data were used to identify the precipitating particles and to characterize their energy, spatial distribution and temporal variation over Antarctica during this isolated storm. Both the ozone decrease and nitric oxide increase initiate with the onset of the storm, and persist for several days after the precipitation ends, descending in the downward flow of the polar vortex. These combined data present a unique case study of the temporal and spatial morphology of chemical changes induced by electron precipitation during moderate geomagnetic storms, indicating that these commonplace events can cause significant effects on the middle mesospheric ozone distribution.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; mikrobølge; ozonlaget; radiometer

Polar operations in Antarctica – operating the Troll Research Station, Dronning Maud Land - Mikelborg, Øystein; Pedersen, Ken (Fram forum, 2012)
Keywords: Dronning Maud Land; Troll forskningsstasjon; ekspedisjoner; logistikk; polarområdene

Atmospheric mercury observations from Antarctica: seasonal variation and source and sink region calculations - Pfaffhuber, Katrine Aspmo; Berg, Torunn; Hirdman, D; Stohl, Andreas (Atmospheric Chemistry and Physics (Print), 2012)
Long term atmospheric mercury measurements in the Southern Hemisphere are scarce and in Antarctica completely absent. Recent studies have shown that the Antarctic continent plays an important role in the global mercury cycle. Therefore, long term measurements of gaseous elemental mercury (GEM) were initiated at the Norwegian Antarctic Research Station, Troll (TRS) in order to improve our understanding of atmospheric transport, transformation and removal processes of GEM. GEM measurements started in February 2007 and are still ongoing, and this paper presents results from the first four years. The mean annual GEM concentration of 0.93 ± 0.19 ng m−3 is in good agreement with other recent southern-hemispheric measurements. Measurements of GEM were combined with the output of the Lagrangian particle dispersion model FLEXPART, for a statistical analysis of GEM source and sink regions. It was found that the ocean is a source of GEM to TRS year round, especially in summer and fall. On time scales of up to 20 days, there is little direct transport of GEM to TRS from Southern Hemisphere continents, but sources there are important for determining the overall GEM load in the Southern Hemisphere and for the mean GEM concentration at TRS. Further, the sea ice and marginal ice zones are GEM sinks in spring as also seen in the Arctic, but the Antarctic oceanic sink seems weaker. Contrary to the Arctic, a strong summer time GEM sink was found, when air originates from the Antarctic plateau, which shows that the summertime removal mechanism of GEM is completely different and is caused by other chemical processes than the springtime atmospheric mercury depletion events. The results were corroborated by an analysis of ozone source and sink regions.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; miljøgifter; ozonlaget

Direct observations of nitric oxide produced by energetic electron precipitation into the Antarctic middle atmosphere - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Holmén, Kim; Horne, Richard B (Geophysical Research Letters, 2011)
We report the first ground-based passive microwave observations made from Troll station, Antarctica, which show enhanced mesospheric nitric oxide (NO) volume mixing ratio reaching levels of 1.2 ppmv, or 2–3 orders of magnitude above background, at 70–80 km during small, relatively isolated geomagnetic storms in 2008. The mesospheric NO peaked 2 days after enhanced NO at higher altitudes (110–150 km) measured by the SABER satellite, and 2 days after peaks in the >30 keV and >300 keV electron flux measured by POES, although the 300 keV electron flux remained high. High time resolution data shows that mesospheric NO was enhanced at night and decayed during the day and built up to high levels over a period of 3–4 days. The altitude profile of mesospheric NO suggests direct production by ∼300 keV electron precipitation. Simulations using the Sodankylä Ion and Neutral Chemistry model show that the delay between thermospheric and mesospheric NO enhancements was primarily a result of the weaker production rate at lower altitudes by ∼300 keV electrons competing against strong day-time losses.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; meteorologi; observasjoner; radiometer

Tracing biomass burning aerosol from South America to Troll Research Station, Antarctica - Fiebig, Markus; Lunder, Chris René; Stohl, Andreas (Geophysical Research Letters, 2009)
The atmospheric observatory at the Norwegian Research Station Troll in Queen Maud Land, Antarctica, holds, since February 2007, the first all-year Antarctic atmospheric aerosol particle number size distribution measurements. These are colocated with measurements of the aerosol absorption and spectral scattering coefficients. In June 2007, this instrument set observed an aerosol whose properties were indicative of a biomass burning aerosol. These properties included two log-normal size distribution modes with median particle diameters of 0.105 μm and 0.36 μm, sharply falling off to smaller and larger sizes, and peaks in scattering and absorption coefficient. With backward plume calculations of the Lagrangian transport model FLEXPART and the MODIS fire activity product, a source-receptor relationship was established between biomass burning events in Central Brazil and the aerosol seen at Troll. This is the first direct evidence that the Antarctic continent is susceptible to emissions from as far north as Southern tropical latitudes.
Keywords: Dronning Maud Land; Troll forskningsstasjon; biomasse; klimatologi; meteorologi; utslipp

Atmospheric monitoring at the Norwegian Antarctic station Troll: measurement programme and first results - Hansen, Georg; Aspmo, Katrine; Berg, Torunn; Edvardsen, Kåre; Fiebig, Markus; Kallenborn, Roland; Krognes, Terje; Lunder, Chris; Stebel, Kersten; Schmidbauer, Norbert; Solberg, Sverre; Yttri, Karl Espen (Polar Research, 2009)
The Troll Atmospheric Station in Antarctica (72°01'S, 2°32'E, 1309 m a.s.l.) was established and put into operation in early 2007. The main foci of the measurement programme are pollution and aerosols in the transition zone between the coastal zone and the inland ice plateau, complementing existing observation programmes along the Antarctic coast and on the Antarctic Plateau. After one year of operation, the monitoring programme is fully operative, and a comprehensive set of data is being analysed. As far as comparable data are available, there is satisfactory agreement between previous and new data. Both aerosol data and measurements of pollution indicate the episodic influence of coastal air masses throughout the year. Background values of medium long-lived pollutants such as CO, O3 and Hg are up to 50% lower than at corresponding Arctic sites (depending on the season), but are still significant. Total ozone and UV doses manifest the recurring Antarctic stratospheric ozone hole, which was moderately severe, but very persistent in 2007. Specific episodes of elevated aerosol concentration and mercury activation are currently under detailed investigation, and will be published separately.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; meteorologi; målinger; ozonlaget

Observasjoner av atmosfæriske parametere ved Troll-stasjonen i Antarktis - forskning og overvåkning basert på lange tidsserier. Fase 1 (2005/06) - NFR/NARE prosjekt 168908/S30 - Hansen, Georg Heinrich; Aspmo, Katrine; Berg, Torunn; Edvardsen, Kåre; Fiebig, Markus; Kallenborn, Roland; Lunder, Chris Rene; Nilsen, Tore; Schmidbauer, Norbert; Solberg, Sverre; Stebel, Kerstin; Wasseng, Jan; et al. (NILU, 2007)
Fra årsskifte 2006/2007 har den norske Antarktisstasjonen Troll (72º S, 2º E, 1270 m.o.h.) i Dronning-Maud-Land vært en helårsbemannet forsknings-, overvåkings- og servicestasjon. Dette åpnet for muligheten til å gjennomføre kontinuerlige målinger av en rekke viktige atmosfæriske parametre. I februar 2007 ble den nye NILU-atmosfære målestasjonen på Troll satt i gang. Måleprogrammet omfatter optiske, fysiske og kjemiske egenskaper av aerosoler, totalozon og UV-stråling, uorganisk og organisk forurensning inkludert tungmetaller som kvikksølv, samt meteorologiske parametre. Programmet omfatter også oppbyggingen av et luftflaskearkiv. Etter de første 6 månedene med den første Antarktisvinteren ser alle instrumenter ut til å være i meget god tilstand og levererkontinuerlig nye data. Disse analyseres for tiden, og de første resultatene vil bli publisert tidlig i 2008. Måleprogrammet finansieres i all hovedsak gjennom forskningsprogrammet NARE (Norwegian Antarctic Research Expeditions) ved Norsk polarinstitutt.
Keywords: Dronning Maud Land; Troll forskningsstasjon; miljøovervåking; målinger

Jutulsessen: Fimbulheimen (Norsk Polarinstitutt, 1992)
Keywords: Dronning Maud Land; Troll forskningsstasjon; geografi; kartlegging; satellite bilder

Report of the Norwegian Antarctic Research Expedition 1989/90 - Norsk, Polarinstitutt (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; Dronning Maud Land; NARE 1989/90; Troll forskningsstasjon; Weddellhavet; geologi; marin økologi; meteorologi; zoologi